Improving Distributed Cloud Data Engineering with AI-Powered Failure Prediction Systems (International Journal of Scientific Research and Management (IJSRM), 2024)
The exponential adoption of distributed cloud systems has imposed heretofore unseen demands as to data dependability, redundancy, and process performance. The conventional failure detection techniques can only provide a partial solution to the dynamic nature of the Distributed Cloud Environment that requires substantial time and consumes valuable resources. This paper introduces a novel framework that applies AI failure prediction systems to the decentralized cloud data engineering processes. The proposed solutions involve integrating state-of-art machine learning and deep learning techniques with on real-time system analysis and prognostication of potential failures a priori. By following the procedure of combining the system logs with performance parameters and analyzing the patterns of anomaly detection, the framework provides high accuracy and scalability. The evaluation outcome also shows positive developments such as a seventy percent reduction in the downtime, improvement on the data credibility, and efficiency of the resource usage. The previous section presented quantifiable results to back the applicability of the framework and can prove to be a solution for real-world distributed cloud systems in accomplishing optimal cloud data engineering operations with minimum failure effect. In view of this, this research forms a strong background to enhance failure prediction methods in the distributed cloud systems to enhance development of more dependable and efficient cloud environments. Further studies will investigate the integration of hybrid AI models together with the increase in the range of scenarios, which will drive new issues in the distributed cloud environment.